Risks, Violence, Security and Peace in Latin America 40 Years of the Latin American Council of Peace Research (CLAIP) (The Anthropocene: Politik-Economics-Society-Science,, 2018)
This book analyses the war against drugs, violence in streets, schools and families, and mining conflicts in Latin America. It examines the nonviolent negotiations, human rights, peacebuilding and education, explores security in cyberspace and proposes to overcome xenophobia, white supremacy, sexism, and homophobia, where social inequality increases injustice and violence. During the past 40 years of the Latin American Council for Peace Research (CLAIP) regional conditions have worsened. Environmental justice was crucial in the recent peace process in Colombia, but also in other countries, where indigenous people are losing their livelihood and identity. Since the end of the cold war, capitalism aggravated the life conditions of poor people. The neoliberal dismantling of the State reduced their rights and wellbeing in favour of enterprises. Youth are not only the most exposed to violence, but represent also the future for a different management of human relations and nature.